2020
DOI: 10.5430/wje.v10n3p19
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Learning Module of Educational Administration and Educational Institute for Students in Master of Education Degree in Thailand

Abstract: The knowledge creation for the efficiency, quality, and the effectiveness, learning achievement and through learning module the developed learning of Educational Administration and Educational Institute for students. However, knowledge creation also be used to learning module of school-based supervision for students? This paper describes the application of basic knowledge creation on module of “Educational Administration and Educational Institute for students,” in master of Education degree in Thailand. Changi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…They have had their post-test scores significantly 0.1-0.5 higher than their pre-test one (Suda, 2005;Donbundit, 2008;Inruangsri, 2011;Paphaphasid, 2018;Chantarasombat, Udombunyanupab, & Kenchaiyawong, 2018). Moreover, their satisfaction was in the highest level (Hasakool, Chianchana, & Stirayakorn, 2016;Krongtanoen, 2016;Chantarasombat, Udombunyanupab, & Kenchaiyawong, 2018;Chantarasombat, & Meekhamtong, 2020) In semester 1, 2020, we had started the learning module for doctoral students in Educational Administration and Leadership at Northeastern University, Khon Kaen, Thailand, by studying elements and factors including the current and desirable condition of Thai learning management in enhancing the critical thinking of the secondary school teachers before creating the program by using google classroom technique. We used 5 experts and 2 pre-test groups who were not our research population to evaluate our module.…”
Section: Introductionmentioning
confidence: 99%
“…They have had their post-test scores significantly 0.1-0.5 higher than their pre-test one (Suda, 2005;Donbundit, 2008;Inruangsri, 2011;Paphaphasid, 2018;Chantarasombat, Udombunyanupab, & Kenchaiyawong, 2018). Moreover, their satisfaction was in the highest level (Hasakool, Chianchana, & Stirayakorn, 2016;Krongtanoen, 2016;Chantarasombat, Udombunyanupab, & Kenchaiyawong, 2018;Chantarasombat, & Meekhamtong, 2020) In semester 1, 2020, we had started the learning module for doctoral students in Educational Administration and Leadership at Northeastern University, Khon Kaen, Thailand, by studying elements and factors including the current and desirable condition of Thai learning management in enhancing the critical thinking of the secondary school teachers before creating the program by using google classroom technique. We used 5 experts and 2 pre-test groups who were not our research population to evaluate our module.…”
Section: Introductionmentioning
confidence: 99%
“…Edmonds (1994) who constructed the learning module for enhancing and encouraging patients being treated by Nitroglycerin, found that the learning module increased their knowledge and morale more than those that only studied through documents at .001 level. In Thailand, there were many studies on the modules found its efficiency in high effectiveness index significantly above the specified criterion 80/80 (Suda, 2005;Donbundit, 2008;Inruangsri, 2011;Krongtanoen, 2016;Hasakool, Chianchana, & Stirayakorn, 2016;Paphaphasid, 2018;Chantarasombat, 2020;and Chantarasombat, & Meekhamtong, 2020). These results seem to confirm the benefit of the learning module, an effective educational innovation, that it could assist students in achieving their full potential and was appropriate for teachers to utilize in the development of students.…”
Section: Introductionmentioning
confidence: 99%
“…The total average in all aspects was at the highest level, and it was at the highest level in every aspect. This is supported by the study from Chantarasombat and Meekhamtong (2019) who conducted research on the development of leader teachers development program in learning Thai management for enhancing critical thinking of students in secondary schools in Educational Administration Seminar Courses for master's degree students majoring in educational administration and found that the efficiency and effectiveness of the developed program were 85.67 (E1) /84.00 (E2) which were higher than the criterion set at 80/80. Laokerd (2016) who studied the development of a virtual community-based learning system to promote knowledge and competency of educational innovation and information technology for student teachers in public higher education institutions also stated that there were 6 important elements including 1) society relationships, 2) membership, 3) sharing, 4) resource, 5) presentations, and 6) evaluation.…”
Section: Research Resultsmentioning
confidence: 89%